Safe corridor for the implantation of thoracolumbar pedicle screws in growing pigs: A morphometric study - Cachon, Thibaut (PLoS One, 2017)
The pig spine is widely used as a large animal model for preclinical research in human medicine to test new spinal implants and surgical procedures. Among them, pedicle screw is one of the most common method of fixation of those implants. However, the pedicle of the porcine vertebra is not as well defined and not as large as the pedicle of the human vertebra. Therefore, the position of the screw should be adapted to the pig and not merely transposed based on the literature on humans. The purpose of this study is to determine the characteristics of the optimum implantation corridors for pedicle screws in the thoracolumbar spine of piglets of different ages using computed tomography (CT) and to determine the size and length of these corridors in pigs of different ages. CT scans from five groups of age: 6, 10, 14, 18, and 26 weeks were reviewed. For each thoracolumbar vertebrae, the pedicle width, pedicle axis length, and the pedicle angle was measured for the left and right pedicle. A total of 326 thoracic vertebrae and 126 lumbar vertebrae were included in the study. Pedicles are statistically larger but not longer for the lumbar vertebrae. An important variation of the pedicle angle is observed along the spine. In all pigs, an abrupt modification of the pedicle angle between T10 and T11 was observed, which corresponds to the level of the anticlinal vertebra which is the vertebra for which the spinous process is nearly perpendicular to the vertebral body. In conclusion, this study provides a quantitative database of pedicle screw implantation corridors in pigs of different ages. When using pedicle screws in experimental studies in pigs, these results should be considered for selecting the most suitable implants for the study but also to ensure a correct and safer screw position. Improving study procedures may limit postoperative complications and pain, thereby limiting the use of live animals.